Mothers’ Experience and Perceived Barriers to Practice Healthy Feeding to Their School Going Children - Shahrin, Tunazzina; Paul, Bijoy Kumer; Sharmin, Saida; Begum, Munira; Jahan, Nusrat; Nusrat, Farzana; Rahman, Moyeedur (Community Based Medical Journal, 2023)
A cross-sectional study was conducted between January and December of 2018 in some randomly selected schools under Dhaka City Corporation, Bangladesh, to examine mothers’ experience and their perceived barriers to practice healthy feeding to their school going children. We adopted convenient sampling technique. A total of 120 mothers participated in this study who had children aged between six and eight years. A pre-tested, semi-structured questionnaire was used for data collection. Questionnaire was formatted in both Bangla and English language. However, the participants chose Bangla version for filling up the survey questionnaire. A modified Likert’s scale was used. Socio-demographic variables, mothers’ feeding practice and perceived barriers were analysed using descriptive statistics. 58.2% of the participants belonged to 30-35 years age group, while 41.8% to 36-40 years age group. Among them, higher secondary passed 3.4%, while 35.3% had their university graduation, and 61.3% completed postgraduation. 6.7% had poor economic status, while 73.3% were semi-elite and 20% were from elite income group. Among them, 75% were Muslim, 14.2% Hindu, 7.5% Christian and 3.3% Buddhist. 21.7% of the mothers found availability of healthy food as 'very easy' and 66.7% found it 'easy', while 9.2% found it 'difficult'; only 2.5% found it 'very difficult'. Only 11.6% of the mothers found preparation of healthy meal inconvenient, while 71.7% found it convenient and 16.7% found it very convenient. Regarding taste of a healthy meal, 2.5% reported as 'very monotonous', 37.5% as 'monotonous', 54.2% reported as 'charming' and only 5.8% stated it as 'very charming'. Preparation cost of a healthy meal was reported as costly by only 15.8% of the mothers, while cost effective by 76.7%, and very cost effective by the rest 7.5%. 42.4% of the mothers stated that their children have the habits of taking meal sitting with the family members, while 48.8% were fed while watching TV, and 8.8% reported that they fed their children while they were playing. Only 37.5% of mothers reported that their children found it pleasant taking healthy food. Regarding time spent on feeding the children, 17.5% stated 'very time consuming', while 68.3% stated 'time consuming', and only 14.2% found it 'timesaving'. Only 20.8% of mothers reported that they could conveniently feed their children healthy food. Difficulties experienced by the mothers were strong aversion (15.8%), fast food preference (22.5%), varieties of food preference (61.7%). CBMJ 2023 January: Vol. 12 No. 01 P: 93-98